化简(m+2n-3p)2-(m-2p)(m-n)
1个回答
原式=2m+4n-6p-(m^2-mn-2mp+2np)
=2m+4n-6p-m^2+mn+2mp-2np
=m^2+2mp-2np+2m+4n-6p
相关问题
已知m,n,p满足|2m|+m=0,|n|=n,p•|p|=1,化简|n|-|m-p-1|+|p+n|-|2n+1|.
已知m、n、p满足|2m|+m=0,|n|=n,p|p|=1.化简:|n|-|m-p-1|+|p+n|-|2n+1|.
M+2N-P=M+() m-2n+p=m-() m-2n-p=m-() m+2n+p=m-()
(m-2n-p)(m-2n+p)-(m+2n+p)(m+2n+p)
已知实数m,n,p在数轴上的位置如图2所示,化简√m^2-√(p-m)^2+√(p-n)^2-|-n|
计算或化简 (3m-n)(-3m-n)-(m-2n)^2-(m-2n)(2m-n)
化简分解:(3m-2n)²+(3m+2n)(3m-2n)-9(m+n)²
化简:(m-n)(m+n)+(m+n)2-2m2
2(m+n)2-(m+n)+4(m+n)-(m+n)2+3(m+n)2 化简求值
(2m+n-p)( 2m+p-n)